ANALISIS SISTEM ARSIP DI KANTOR REGIONAL SEKRETARIAT PEMERINTAH KABUPATEN BATU BARA - Muhammad Dedi Irawan (Universitas Asahan, 2019)
Abstract - This research is done because the processing of archiving is still done manually, this is very difficult and slow in searching if needed. Archiving a few months or even years ago will certainly be difficult to find because of the accumulation of files or because the archive has been damaged. The difficulty and complexity can be overcome by using WEB-based and MySql databases to manage archives. Management utilizing WEB-based and MySql databases are no longer in the form of archive sheets but have been in the form of scanned files from the original archive. The scanned archive will be stored with certain codes to make it easier to search so that the archives that came in a few months or even years ago are undamaged and easy to find. Keywords - Archiving, Analysis, The Batu Bara Regency